Perspective: Lessons from COVID-19 of countries in the European region in light of findings from the health system response monitor - Tille, Florian; Van Ginneken, Ewout; Winkelmann, Juliane; Hernandez-Quevedo, Cristina; Falkenbach, Michelle; Sagan, Anna; Karanikolos, Marina; Cylus, Jonathan (Frontiers in Public Health, 2023)
Introduction Decision-makers initially had limited data to inform their policy responses to the COVID-19 pandemic. The research community developed several online databases to track cases, deaths, and hospitalizations; however, a major deficiency was the lack of detailed information on how health systems were responding to the pandemic and how they would need to be transformed going forward. Approach In an effort to fill this information gap, in March 2020, the European Observatory on Health Systems and Policies, the WHO European Regional Office and the European Commission created the COVID-19 Health System Response Monitor (HSRM) to collect and organize up-to-date information on how health systems, mainly in the WHO European Region, were responding to the COVID-19 pandemic. Findings The HSRM analysis and broader Observatory work on COVID-19 shone light on a range of health system challenges and weaknesses and catalogued policy options countries put in place during the pandemic to address these. Countries prioritised policies on investing in public health, supporting the workforce, maintaining financial stability, and strengthening governance in their response to COVID-19. Outlook In support of countries, the COVID-19 HSRM will remain available as a repository to inform decision makers on options for actions and possible measures against COVID-19 and other public health emergencies. Building on its previous work on health systems resilience, the European Observatory on Health Systems and Policies will sustain its focus on analysing key issues related to the recovery from the pandemic and making health systems more resilient, including systematic resilience testing.